2012
DOI: 10.1100/2012/842727
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Identification for Prostate Cancer and Lymph Node Metastasis from Microarray Data and Protein Interaction Network Using Gene Prioritization Method

Abstract: Finding a genetic disease-related gene is not a trivial task. Therefore, computational methods are needed to present clues to the biomedical community to explore genes that are more likely to be related to a specific disease as biomarker. We present biomarker identification problem using gene prioritization method called gene prioritization from microarray data based on shortest paths, extended with structural and biological properties and edge flux using voting scheme (GP-MIDAS-VXEF). The method is based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In addition, we analyzed XPNPEP2 gene alterations using data extracted from the cBioPortal online analysis tool and found that metastatic prostate cancer has the highest frequency of XPNPEP2 gene amplification 17,18 . Using a gene prioritization method (GP-MIDAS-VXEF) to compare prostate cancer and lymph node metastasis, Carlos Roberto Arias et.al demonstrated that XPNPEP2 is a metastatic gene candidate 19 . Additionally, Cheng te.al revealed that XPNPEP2 facilitated cervical cancer cell invasion and migration by inducing epithelial-mesenchymal transition 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we analyzed XPNPEP2 gene alterations using data extracted from the cBioPortal online analysis tool and found that metastatic prostate cancer has the highest frequency of XPNPEP2 gene amplification 17,18 . Using a gene prioritization method (GP-MIDAS-VXEF) to compare prostate cancer and lymph node metastasis, Carlos Roberto Arias et.al demonstrated that XPNPEP2 is a metastatic gene candidate 19 . Additionally, Cheng te.al revealed that XPNPEP2 facilitated cervical cancer cell invasion and migration by inducing epithelial-mesenchymal transition 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein interaction networks in combination with gene expression data have been used to identify biomarkers associated with cancer metastases. 2 Another approach is to identify subcategories of a cancer and the associated biomarkers for each category, so as to allow treating a patient based on the cosegregation of her/his cancer profile within one cancer subcategory. Recently, subgroup-specific biomarker networks have been shown to predict glioblastoma prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Arias et al (2012) identified biomarkers for prostate cancer and lymph node metastasis from microarray data and the protein interaction network using the gene prioritization method. A protein-protein interaction network of established miRNA targets confirm that these proteins are highly connected and essential to the cell, affecting tumorigenesis, cell growth/proliferation, cellular death, cell assembly, and maintenance pathways (Budd et al, 2012).…”
mentioning
confidence: 99%